ROMANIAN JOURNAL OF POPULATION STUDIES, SUPPLEMENT. 2011, (POPULATION AND ECONOMY. RURAL AND URBAN INSTANCES) - BALOG, Iosif Marin; LUMPERDEAN, Ioan; GRÄF, Rudolf; BOLOVAN, Ioan (2012)
Romanian Journal of Population Studies is published twice yearly by the Centre for Population Studies. The Centre for Population Studies functions inside Babeş-Bolyai University of Cluj-Napoca since 2002 and it aims at the optimisation of the main programs of scientific research at national level and the involvement in international research programs, as well as a more active presence of the University in the public life. The Centre for Population Studies was evaluated by the National Council of Scientific Research for Superior Education (CNCSIS) and got the official recognition in 2004.